The role of LSR gene variants in early onset intrahepatic cholestasis: a case series with treatment options - Ohlsson, Sinja; Zaufel, Alex; Qvartskhava, Natalia; Stock, Friedrich; Hinreiner, Sophie; Baba, Hideo A.; Prusinskas, Benas; Kubitz, Ralf; Görg, Boris; Herebian, Diran; Lainka, Elke; Kathemann, Simone (Frontiers in Pediatrics, 2025)
We report on three children with novel variants in the lipolysis-stimulated lipoprotein receptor (LSR) gene with clinical presentation with early onset intrahepatic cholestasis and the main symptom being uncontrollable itching. Two patients showed dystrophy, short stature and microcephaly, whilst one patient had neurological developmental delay. LSR is one component of special tricellular tight junctions (tTJs) with expression in the liver and brain. We analyzed clinical data for all patients and performed multigene panel sequencing followed by Human Phenotype Ontology (HPO) based exome analysis, classifying the sequenced variants according to the American College of Medical Genetics and Genomics (ACMG) guidelines. We performed immunostaining on the liver cryosections. The lack of LSR expression in immunofluorescence of the patients’ liver tissue confirmed the pathogenicity of genetic variants. We analyzed bile acids (BA) and their derivatives by ultra-performance liquid chromatography-mass spectrometry (UPLC-MS) in two of the three patients, confirming disturbed bile salt secretion. We also describe the use of an ileal bile acid transport (IBAT) inhibitor in two patients with LSR-associated intrahepatic cholestasis for the first time. Both patients showed a good response to the therapy in terms of itch control. In conclusion, LSR-associated early onset intrahepatic cholestasis is a new and likely underdiagnosed disease. Patients with an unclear progressive familial intrahepatic cholestasis (PFIC)-like clinical picture should therefore undergo genetic testing of the LSR gene. Treatment with an IBAT inhibitor should be considered.